Azaphosphatranes Catalyzed Strecker Reaction in the Presence of Water. Issue 46 (10th December 2020) - Yang, Jian; Manick, Anne‐Doriane; Li, Chunyang; Bugaut, Xavier; Chatelet, Bastien; Dufaud, Véronique; Hérault, Damien; Martinez, Alexandre
Abstract: Azaphosphatranes were found to act as efficient organocatalysts in the presence of water for the cyanation of differently substituted imines. A relatively safer source of cyanide, trimethylsilyl cyanide (TMSCN), was used, and excellent yields could be obtained with only 0.05 mol % of catalyst. The influence of acidity of azaphosphatranes on catalytic activity as well as the role of azaphosphatranes in the mechanism of the reaction were also investigated. Abstract : Azaphosphatranes display high catalytic activities for the Strecker reaction: only 0.05 mol % of organocatalyst is necessary to achieve quantitative yields in 2 h at 0 °C. High TON and TOF are reached, associated with high selectivity since no by‐product can be observed. In addition, azaphosphtranes are less difficult to synthesize and much more practical to handle than the pro‐azaphosphatrane bases.